Interrogating patient-centredness in undergraduate medical education using an integrated behaviour model - Elize Archer; E M Bitzer; B B Van Heerden (South African Family Practice)
Background: Patient-centredness, an approach that puts the patient at the centre of the consultation, thus focusing on patients instead of on his/her diseases, has been identified by most medical schools as a desired core competence of their graduates. Despite some curriculum initiatives, medical students often display a lack of patient-centredness upon graduation. This bears reason for concern and it was thus deemed important to explore possible factors that influence the teaching and learning of patient-centredness in an undergraduate medical curriculum. The article suggests a framework that can assist programme developers to conceptualise the teaching and learning of patient-centredness across an undergraduate curriculum.